Capacitance of Film Structures Including Graphitic Carbon Nitride - V. T. Pham; S. E. Maximov; E. A. Utkina; E. B. Chubenko; V. E. Borisenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2024)
Al/g-C3N4/Si/Al, Al/g-C3N4/SiO2/Si/Al, Al/g-C3N4/Al and Al/g-C3N4/Al2O3/Al structures were fabricated by rapid chemical vapor deposition of graphitic carbon nitride (g-C3N4) from melamine onto silicon (Si) and aluminum (Al) substrates partially coated with appropriate oxide – SiO2 or Al2O3 – and Al contacts deposited on the surface. Their capacitance-voltage characteristics and frequency dependence of the capacitance were measured at room temperature. It was found that the permittivity of g-C3N4 is 14 in structures on silicon and 9–10 in structures on aluminum. The decrease in permittivity is explained by the formation of Al2O3 at the g-C3N4/Al boundary during the deposition of g-C3N4, as indicated by the results of the X-ray diffraction analysis of the formed samples.